Astaxanthin-enriched shrimp shell oil as natural preservative in Notopterus chitala fish balls - Nguyen, Duy Tan; Tran, Chi Hai; Phan, Van Man (Agriculture and Natural Resources, 2026)
Importance of the work: Shrimp oil enriched with astaxanthin, derived from black tiger shrimp (Penaeus monodon Fabricius, 1798) shells, possesses strong antioxidant and antimicrobial properties. Its application as a natural preservative could enhance the quality and shelf life of f ish-based products, offering a sustainable alternative to synthetic additives. Objectives: To evaluate the effects of astaxanthin-rich shrimp oil on antioxidant and antimicrobial activities, as well as its influence on the physicochemical, textural, sensory and microbiological properties of Notopterus chitala (Hamilton, 1822) fish balls during refrigerated storage. Materials and Methods: Shrimp oil was extracted from shrimp shells and analyzed for astaxanthin content and antioxidant activity (IC50 ). The oil was incorporated into fish ball formulations at concentrations of 0–3.5%. Physicochemical parameters (pH, peroxide value, TBARS, sulfhydryl content), texture (gel strength, water-holding capacity), color, sensory attributes and microbial stability (total viable count) were monitored over 12 days of chilled storage. Results: The shrimp oil contained 142 µg/g astaxanthin and demonstrated strong radical scavenging activity (half maximal inhibitory concentration = 25.12 µg/mL) and antimicrobial activity against Staphylococcus aureus. Incorporation at 2.0–2.5% improved the gel strength, water-holding capacity and sensory acceptability. During storage, 2.5–3.5% supplementation effectively reduced pH decline, lipid and protein oxidation and microbial growth, showing preservative effects comparable to the synthetic antioxidant butylated hydroxytoluene. Main finding: Astaxanthin-enriched shrimp oil, effectively enhanced the oxidative stability, inhibited microbial growth and maintained the physicochemical, textural and sensory qualities of N. chitala fish balls during refrigerated storage. At optimal incorporation levels, the preservative performance of the astaxanthin-enriched shrimp oil was comparable to that of synthetic antioxidants, highlighting its potential as a natural and sustainable alternative for seafood preservation.